The Psychological Meaning Of Color In Design: A Semantic Review - Meliksetyan, Gor (Զանգակ հրատ.)
Color is a fundamental and pervasive element of human perception and a critical tool in various design disciplines. This review synthesizes the scientific literature on the psychological meaning of color within design contexts, encompassing graphic, web, interior, product, and marketing design. The study examines how color influences human emotion, cognition, and behavior, drawing upon theoretical frameworks ranging from biological and evolutionary perspectives to learned associations and context-dependent models, particularly the Color-in-Context theory. The methodology involved a systematic review of peer-reviewed journal articles, academic books, and conference proceedings, focusing on empirical research employing experimental, correlational, survey, and qualitative methods. Key findings indicate that colors such as red, blue, green, yellow, black, and white evoke complex, often dualistic psychological responses (e.g., red signifies both passion and danger; blue conveys trust but also sadness). These responses are significantly moderated by factors including the specific design context, cultural background, individual differences (age, gender, personality, experience), and the interplay of color combinations, saturation, and brightness. Methodological limitations within the field, such as inadequate color specification and control, underpowered samples, and oversimplification of stimuli, are identified. Practical implications for design professionals highlight the need for nuanced, evidence-based color strategies that consider context, target audience, and brand identity, alongside ethical considerations regarding potential manipulation and accessibility. The review concludes that while color demonstrably affects psychological functioning, the field requires further research with improved methodological rigor, a greater focus on moderating variables and complex color interactions, and the development of mid-level theories to bridge the gap between fundamental research and effective design application.
Keywords: Psychology